An historical examination of the evolution of student activism at the University ff Limpopo (formely known as the University of the North),1968 to 2015 - Vuma, Sethuthuthu Lucky (My University, 2022)
The problem under investigation in this thesis is centred on the complex changes and transformation in student activism at the University of Limpopo (UL) during the period 1968-2015. The overreaching objectives of the study were to unpack the changing conceptualisation of student politics, tactics and strategies deployed in realising student needs and interests in the creation of South Africa’s contested transition from the openly racist apartheid system to a liberal democratic regime enshrined in the 1996 constitution. Periodisation theory, which conceptualises and frames development or change and transformation of historical phenomena as unfolding in terms of distinctive time periods, was used to provide historical insight into the evolution of student activism. The cognitive merits and possibilities of periodisation theory were enhanced by integrating Altbach’s Theory of Student Activism, which stresses the Importance of recognising and grasping the unique characteristics of student activists and their organisations in higher education systems. The resultant theoretical framework produced a cognitive structure which provided the researcher with concepts and ideation to make sense of the difficult and complex reconfiguration demanded, especially by the transition. The methodology utilised in the study involved collecting and analysing data from both primary and secondary sources. The primary data was acquired from a sample of former students who were registered at UL during the period covered by the study. The Thematic Content Analyses (TCA) approach distilled themes embedded in the data collected. An overreaching finding of the study is that while it was relatively easy for Black students to conceptualise and decode the nature of oppression and struggle in an openly racialised system, such as apartheid, the ascendance to state power of Black leaders of liberation movements, some of whom were militant student activists prior to 1994, created a political landscape which made it difficult for students to decode what was required to deepen liberation and freedom. Some of the difficulties manifested themselves inter alia in the scandalous vandalisation of University resources, such as libraries, cars and classrooms. More than twenty years into “democracy”, however, student activists began to penetrate and decode deeper layers of oppression, hidden by the dense fog of liberal democracy, which needed to be dismantled. It is in this sense that the thesis views the eruption of the 2015 #Fees Must Fall movement and the accompanying curriculum decolonisation battles in South Africa as constituting a revolutionary landmark in the evolution of student activism. Student activists since 2015 seemed to have come to the realisation that liberal democratic rights and freedoms were incapable of dismantling white supremacy (racism), which is at the heart of the subjugation and oppression of Black people in South Africa and beyond. The thesis recommends, inter alia, that the relative invisibility of the role of women in studies of this nature is troubling and that historians must urgently solve this lacuna
Thesis (Ph.D.(History)) -- University Of Limpopo, 2022
Keywords: Student politics; Racist apartheid; Democratic regime; Student activism; Student movements; College students -- Political activity -- South Africa; Student movements -- South Africa -- History